How to manage an aid exit strategy : the future of development aid - Fee, Derek, 1947- (London ; New York : Zed Books, 2012)
"After almost forty years of development aid most commentators agree that aid as we know it has not worked. Aid fatigue is suffered on both the donor and recipient sides, with a wide divergence between those who call for a radical overhaul of aid delivery methods, those who advocate a complete end to development aid and those who continually demand significant increases in aid flows. How to Manage an Aid Exit Strategy provides a refreshing, insightful and comprehensive analysis of how an exit may actually be possible - drawing on real experience and as such supplying a simple summary of recommended policy steps. The author thoroughly reviews aid for trade, regional integration and microfinance and a host of other solutions that have been proposed - arguing that an exit strategy for both donors and the least developed countries will have to consider the optimal combination of these specific initiatives to best satisfy the necessity of development and at the same time solve the problems of conventional aid."--Publisher's website.
The state of aid -- A short history of development aid -- The development aid business -- Domestic resource mobilization -- Trade liberalization -- The BRICS -- Regional integration -- Microfinance -- Remittances -- Non-governmental organizations and philanthropic foundations -- Towards an aid exit strategy.
Includes bibliographical references (p. [234]-246) and index.
Keywords: Economic assistance -- Developing countries; Economic development -- Developing countries; Economic assistance -- Developing countries -- History; Economic development -- Developing countries -- Finance -- History